Es deslinde de la frontera en Pirineos centrales (1857-1863) - Capdevila Subirana, Joan (Geographicalia, 2014)
The formal demarcation Spanish-French border took place in mid nineteenth century, between 1853 and 1868, and was reflected in the number of international agreements known as Border Treaties of Bayonne. The work was carried out by the Joint Boundary Commission that, from the Bay of Biscay to the Mediterranean, defined 685 km international boundary line and built 663 border signs. The resulting line would follow the spirit of the Treaty of the Pyrenees (1659) but, above all, solve the various problems arising from border, mostly related to economic exploitation of the environment. The Pyrénées tranche, which corresponds to the provinces of Huesca and Lleida, was the subject of the Boundary Treaty of 1862 and the corresponding Annex to the minutes of demarcation of 1863. In this paper we present the work of the Joint Boundary Commission, the negotiations had to be carried out as and how they were resolved.
Keywords: Border demarcation; nineteenth century; Pyrenees; pastures